Upaya Peningkatan Pengetahuan Remaja Putri Melalui Penyuluhan Keputihan (Flour Albus) Pada Siswi Madrasah Aliyah Negeri (MAN) Sintang - Elvi Juliansyah; Salma Zulfani (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
Reproductive health in the early years of changes in the reproductive system during early adolescence, the development of the reproductive system in humans, both men and women for human survival. Lack of information and knowledge about changes in the reproductive system in adolescence creates anxiety and shame because they are different from their peers. The method used to determine the problem, problem solving, alternative problem solving, method of activities in order to solve the problem. Results and discussion of the prevalence of vaginal discharge increased in 2002, 50% of women in Indonesia had experienced vaginal discharge. Then in 2003, 60% of women had experienced vaginal discharge, this is due to the low knowledge of women having vaginal discharge, for reproductive health. The implementation of vaginal discharge counseling is carried out due to the low knowledge of young women regarding reproductive health, as well as the impact that will occur if reproductive health is not considered for the health of young women in the future. The conclusion there is a change in knowledge, attitudes and views of Sintang State Madrasah Aliyah (MAN) students about flour albus to prevent pathological leucorrhoea by changing risky behavior to maintain genital health.